If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+3v=3(v+2)
We move all terms to the left:
6+3v-(3(v+2))=0
We calculate terms in parentheses: -(3(v+2)), so:We get rid of parentheses
3(v+2)
We multiply parentheses
3v+6
Back to the equation:
-(3v+6)
3v-3v-6+6=0
We add all the numbers together, and all the variables
=0
v=0/1
v=0
| -3(t-5)+7t=6t-9 | | (c+9)(c-12)=0 | | Y=3(-3y-5)+5 | | 3-1/4x=20 | | 39+4x=1 | | k-(8)/4=11 | | 4s+10=2s=-2 | | 3x-76=24-2x | | 50-1/6x=20 | | 18-8y=24 | | 2x16=2/5x | | 4(3k-7)-5=11+k | | 7x+5-x=6x+5 | | (8x-5)+65=180 | | -2n-8n=-13+7-n-3n | | 6(8m-4)=-24-4m | | 3y+8-y=8+y+5 | | 5/6=x-2/x | | 3+x=-103 | | -2-8=3x+7 | | v+v=2 | | 39+-x=1 | | (7x+1)=(10x-9) | | 1.2m+6=-10 | | 3-x+3x=17 | | 25n+7=18n+28 | | (7x+1)=10x-9) | | 5(3x-2)-7=28 | | 3-8x=72 | | -6(1-3x)=-6(-x+7) | | 5+5x=8x-20 | | t=5;t+38 |